The solution structure of EMILIN1 globular C1q domain reveals a disordered insertion necessary for interaction with the alpha4beta1 integrin. - Verdone, G; Doliana, R; Corazza, A; Colebrooke, SA; Spessotto, P; Bot, S; Bucciotti, F; Capuano, A; Silvestri, A; Viglino, P; Campbell, I; Colombatti, A; et al. (2008)
The extracellular matrix protein EMILIN1 (elastin microfibril interface located protein 1) is implicated in maintaining blood pressure homeostasis via the N-terminal elastin microfibril interface domain and in trophoblast invasion of the uterine wall via the globular C1q (gC1q) domain. Here, we describe the first NMR-based homology model structure of the human 52-kDa homotrimer of the EMILIN1 gC1q domain. In contrast to all of the gC1q (crystal) structures solved to date, the 10-stranded beta-sandwich fold of the gC1q domain is reduced to nine beta strands with a consequent increase in the size of the central cavity lumen. An unstructured loop, resulting from an insertion unique to EMILIN1 and EMILIN2 family members and located at the trimer apex upstream of the missing strand, specifically engages the alpha4beta1 integrin. Using both Jurkat T and EA.hy926 endothelial cells as well as site-directed mutagenesis, we demonstrate that the ability of alpha4beta1 integrins to recognize the trimeric EMILIN1 gC1q domain mainly depends on a single glutamic acid residue (Glu(933)). Static and flow adhesion of T cells and haptotactic migration of endothelial cells on gC1q is fully dependent on this residue. Thus, EMILIN1 gC1q-alpha4beta1 represents a unique ligand/receptor system, with a requirement for a 3-fold arrangement of the interaction site.